The Influence of CAR, LDR and BOPO on ROA at Conventional State-Owned Banks Listed on the Indonesia Stock Exchange - Ferona Gustiana; Ahmad Soleh; Zahra Indah Ferina (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2021)
The purpose of this study was to determine the effect of CAR, LDR and BOPO on ROA at conventional state-owned banks listed on the Indonesia Stock Exchange. The sample in this study were four conventional banks in Indonesia, namely BNI, BRI, BTN and Bank Mandiri. The study was conducted from 2010 to 2019. The data collection method used the documentation method. Data analysis used was multiple linear regression, coefficientof determination and hypothesis testing. From the calculation of the multiple linear regression equation, it can be seen that the effect of CAR, LDR and OEOI on ROAat conventional state-owned banks results in regression test results: Y = 11.602 + 0.01X1 + 0.005 X2 - 0.108 X3. The coefficient of determination obtained by R square is 0.785. This means that X1 (CAR), X2 (LDR) and X3 (BOPO) have an effect on ROA (Y) by 78.5% while the rest (100% - 78.5% = 21.5%) are influenced by variables. others who were not examined in this study. The t test results show that there is a significant effect separately between CAR, LDR and BOPO on ROA at conventional state-owned banks. The results of the F test show a significance value of 0.000, because the significant value is less than 0.05, it means that CAR, LDR and BOPO have a significant effect together on ROA at conventional state-owned banks. Keywords: CAR, LDR, BOPO, ROA 1) The Candidate of Bachelor in Economics (Accounting) 2) Supervisors.